Live Streaming Worship: Solusi GKJ Menara Kasih Salatiga dalam Ibadah di Tengah Pandemi Covid-19 - Tommy Cristovel Tangkey; Mikha Krisnawati; Monika Monika; El Zefani Lovena Wiyono; Putri Hergianasari (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2022)
Live-Streaming technology is one of the important methods in church service amid the Covid-19 pandemi. The purpose of community service at GKJ Menara Kasih is to help make online worship broadcasts live through their YouTube account. This community service uses the Service-Learning method. students practice the knowledge gained from lectures which are then used in helping GKJ Menara Kasih as a target for Integrated Field Practice activities. The result of community service is that the online worship held at GKJ Menara Kasih Salatiga made a real contribution as an effort to comply with government regulations regarding activity restrictions and one of the efforts to reduce the spread of the Covid-19 virus.